2022
DOI: 10.3390/jcdd9020055
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Cardiometabolic Risk Factors in Pregnancy: A Review of Risk Prediction Models Targeting Gestational Diabetes and Hypertensive Disorders

Abstract: Cardiovascular disease, especially coronary heart disease and cerebrovascular disease, is a leading cause of mortality and morbidity in women globally. The development of cardiometabolic conditions in pregnancy, such as gestational diabetes mellitus and hypertensive disorders of pregnancy, portend an increased risk of future cardiovascular disease in women. Pregnancy therefore represents a unique opportunity to detect and manage risk factors, prior to the development of cardiovascular sequelae. Risk prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Accurately predicting GDM incidence based on early pregnancy markers could allow development and implementation of interventions to prevent GDM and its complications. However, most predictive models that rely on established clinical risk factors perform poorly 42 , 43 , and thus, there has been a search for reliable and replicable biomarkers. We found that low levels of circulating IGFBP1 in early pregnancy predict later diagnosis of GDM in a large population-based cohort (Gen3G), with external replication and consistent effect sizes in a separate cohort (MOMS).…”
Section: Discussionmentioning
confidence: 99%
“…Accurately predicting GDM incidence based on early pregnancy markers could allow development and implementation of interventions to prevent GDM and its complications. However, most predictive models that rely on established clinical risk factors perform poorly 42 , 43 , and thus, there has been a search for reliable and replicable biomarkers. We found that low levels of circulating IGFBP1 in early pregnancy predict later diagnosis of GDM in a large population-based cohort (Gen3G), with external replication and consistent effect sizes in a separate cohort (MOMS).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Google Scholar gray literature search was conducted as per Enticott et al 16 . Furthermore, we explored the reference list of all included studies and a recent narrative review 17 . The search strategies were developed following search filters for prognostic and diagnostic studies 18 and by consulting librarians at Monash University, Melbourne, VIC, Australia.…”
Section: Review Question and Search Strategymentioning
confidence: 99%
“…Developing certain complications of pregnancy increases the risk of cardiovascular disease later in life for women. 23,24 The interrelatedness of hyperglycemia, hypertension, hyperlipidemia, and obesity commonly contributes to metabolic syndrome 25 and, ultimately, multisystem pathophysiology that compounds the risk for severe cardiovascular disease and stroke. 26 Often co-occurring with cardiometabolicrelated conditions, preterm birth, GDM, birthing an small-for-gestational-age baby, and hypertensive disorders of pregnancy, including gestational hypertension and preeclampsia, are now recognized as risk enhancers for future cardiovascular disease in women.…”
Section: Cardiometabolic Risk Factors In Pregnancymentioning
confidence: 99%